2021
DOI: 10.1111/jipb.13107
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase XBAT35 mediates thermoresponsive hypocotyl growth by targeting ELF3 for degradation in Arabidopsis

Abstract: Summary Plants are capable of coordination of their growth and development with ambient temperatures. EARLY FLOWERING3 (ELF3), an essential component of the plant circadian clock, is also involved in ambient temperature sensing, as well as in inhibiting the expression and protein activity of the thermoresponsive regulator phytochrome interacting factor 4 (PIF4). The ELF3 activity is subjected to attenuation in response to warm temperature; however, how the protein level of ELF3 is regulated at warm temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…As with hypocotyl nuclei, the 27°C pulse and the elf4-1 mutation had a cumulative effect on ELF3 nuclear accumulation ( Supplemental Figure 1B ). The reduced nuclear accumulation of ELF3 at 27°C is consistent with a recent report that ELF3 is degraded by B-BOX ZINC FINGER PROTEIN 18 (BBX18) and XB3 ORTHOLOG 1 IN ARABIDOPSIS THALIANA (XBAT31) and XBAT35 at warm temperatures ( Zhang et al, 2021a , 2021b ).…”
supporting
confidence: 91%
“…As with hypocotyl nuclei, the 27°C pulse and the elf4-1 mutation had a cumulative effect on ELF3 nuclear accumulation ( Supplemental Figure 1B ). The reduced nuclear accumulation of ELF3 at 27°C is consistent with a recent report that ELF3 is degraded by B-BOX ZINC FINGER PROTEIN 18 (BBX18) and XB3 ORTHOLOG 1 IN ARABIDOPSIS THALIANA (XBAT31) and XBAT35 at warm temperatures ( Zhang et al, 2021a , 2021b ).…”
supporting
confidence: 91%
“…Repetitive tract of polypeptides contributes to the temperature response of the circadian clock ELF3 is critical for circadian gating of ambient light and temperature cues (Covington et al, 2001;Carré, 2002;Thines and Harmon, 2010). It is known that BBX18 interacts with ELF3 in thermomorphogenesis, and BBX18 and E3 ligases XBAT31, XBAT35 promote ELF3 protein degradation during warm night (Ding et al, 2018;Zhang et al, 2021a;Zhang et al, 2021b). Recent research has found that ELF3 proteins in vivo usually diffuse at 22°C, but higher ambient temperature induces ELF3 to aggregate into speckles or liquid droplets (Jung et al, 2020).…”
Section: Temperature Compensation Of Circadian Period Lengthmentioning
confidence: 99%
“…The seeds were sown on half-strength Murashige and Skoog (MS) medium with vitamins (containing 1.2% w/v sucrose and 0.8% w/v agar, pH 5.7) and stratified at 4°C for 2 d, after which they were transferred to a standard plant incubator at 22°C under a 16-h-light/8-h-dark photoperiod (long-d conditions) and 60% relative humidity. For phenotypic assays, seedlings were grown at 22°C for 3 d and transferred to 29°C or maintained at 22°C for 4 d. To measure hypocotyl length, the seedlings were photographed, and the hypocotyl lengths of the seedlings were measured using ImageJ software (Zhang et al, 2021b(Zhang et al, , 2021c. All primers used in this study are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…phyB, a well‐known photoreceptor, rapidly reverts from its active form Pfr to its inactive form Pr under warm temperature conditions (Klose et al, 2020), which reduces its inhibition of PIF4 (Jung et al, 2016; Legris et al, 2016). ELF3 undergoes liquid–liquid phase separation (deactivation) and ubiquitin‐mediated degradation under warm temperature conditions (Jung et al, 2020; Zhang et al, 2021b, 2021c), both of which release the inhibitory effects of ELF3 on PIF4 (Nomoto et al, 2012; Box et al, 2015; Nieto et al, 2015; Jung et al, 2020; Silva et al, 2020). PIF7 was recently reported as a new type of thermosensor in Arabidopsis (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%